Analiza popytu pośredniego gospodarki żywnościowej w Polsce w świetle przepływów międzygałęziowych w latach 1990-2000 - Kujaczyński, Tomasz (The Analysis of the Demand for Production Goods in the Polish Agricultural Economy in the Input - Output Model During 1990-2000, 2006)
In 1990-2000 the agricultural economy was characterised by very variable conditions of activity. At the same time there were no considerable changes in the main streams of demands for production goods (agriculture - the food processing industry). The use of production goods in agriculture indicates the decrease of the added value and in consequence the reduction of the income of resources. But such a situation was restrained in the food processing industry.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 503-507